Assessing the International Comovement of Equity Returns - Abate, Girum Dagnachew (World Bank, Washington, DC, 2018)
The international comovement of equity returns has been viewed as reflecting either pervasive common shocks or local linkages between countries. This paper brings these perspectives together by assessing the comovement of equity returns in a dynamic model that allows for both common factors and spatial dependence, using quarterly data for 40 advanced and emerging countries over the past two decades, and including GDP growth, the real interest rate, and credit as fundamental variables. Estimation results employing a bias-corrected quasi-maximum likelihood approach provide strong indication that the cross-country dependence of equity returns results from both spatial effects and common shocks captured by a latent common factor -- weak and strong dependence, respectively. The factor exhibits a robust negative correlation with market measures of aggregate risk. Countries' exposure to the common factor rises with their extent of trade openness and the degree of rigidity of their exchange rate regime. Despite its simplicity, the empirical model fits the data well. All these results are robust to the use of alternative spatial weight matrices. The paper also shows that ignoring cross-country dependence leads to distorted parameter estimates and a marked deterioration of the explanatory power of the empirical model.